Autonomous learning in a PBL approach - ChanLin, Lih-Juan (2021)
This paper reports a case integrating a problem-based learning (PBL) approach with the “Drug & Nutrient Interactions” online course. The main objectives of this PBL approach were to engage students in self-direction, professional reasoning, and self-determination within an autonomous learning setting. The use of the task-oriented learning approach in PBL encouraged students to acquire information skills, including searching, selecting, evaluating, and using information in more meaningful ways. Experience with a PBL approach within a Web-based learning context was obtained. During this study, several types of interactive responses were observed, including discussion related to case selection, information posting and sharing, defining and finalizing, and casual chatting. With the PBL approach, students’ autonomous learning and active involvement in self-direction, professional reasoning, and self-determination in the Web-based interactive activities contributed to successful learning achievements.